Electrical design for ocean wave and tidal energy systems - Alcorn, Raymond; O'Sullivan, Dara (IET renewable energy series ;, 2013)
Renewable energy is expected to play a major part in future energy supplies, both to reduce the impact on the world climate and also to make up for any shortfall in conventional energy sources. Ocean energy has the potential to make a significant contribution to future renewable energy supplies as identified in recent reports from the Intergovernmental Panel for Climate Change and the International Energy Agency. The book gives an electrical engineer's perspective of this technology, addressing offshore wave and tidal power stations, grid integration and distribution. Topics covered include generator selection and rating; electrical energy storage; grid integration; power quality; cabling, umbilicals and array layout; modelling and simulation techniques; control theory and realisation; power system issues; and economics of ocean energy electrical systems.